Public Diplomacy, Soft Power, and Chinese Language in a Campus of Kathmandu, Nepal - Pandit, Kamal (Curriculum Development Journal, 2024)
Public diplomacy is a central pillar of Chinese foreign affairs, with a strong emphasis on people-to-people and cultural diplomacy. Mandarin Chinese, as one of the most widely spoken languages globally, played a significant role in China’s cultural diplomacy efforts. This study examined the role of the Chinese language in fostering China’s soft power in Kathmandu, Nepal, based on data, both interview and records, collected from Bishwo Bhasha Campus. Using César Villanueva Rivas’s framework, which explored how language promotion translates into soft power across five levels—empathetic, sympathetic, geopolitical, diplomatic, and utilitarian—this study found that Mandarin enhances China’s soft power primarily at two levels. First, it increased knowledge and appreciation of Chinese culture, fostering cultural connections (empathetic). Second, it served as a practical tool for economic interactions and opportunities in Kathmandu (utilitarian). These findings highlighted the potential of language learning to act as a bridge for cultural and economic exchange, contributing to China’s public diplomacy efforts in Nepal.